Epidemiological, Clinical and Diagnostic Features of FeLV and FIV: An Updated Review - Canto-Valdés, María Casandra; Bolio-González, Manuel Emilio; Ramírez-Álvarez, Hugo; Cen-Cen, Carlos Josué (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Feline leukemia (FeLV) and immunodeficiency (FIV) viruses are pathogens which affect domestic cats and are classified within the Retroviridae family. These feline retroviruses feature a high capacity of mutation and recombination, which derives in a broad population of viral subtypes with variable pathogenic capacity. These viruses are of great importance in feline health, not only because of the severity of the clinical signs in patients, but also due to the diagnostic complexity which they can pose. The range of prevalence is wide among different studies and geographical zones, probably due to the influence of risk factors, clinical condition of cats and diagnostic tests used. The clinical signs of FeLV disease are variable, depending on the viral subtype and the host’s immune-compromise, as there could be lymphoma, leukemia, red cell aplasia myelosuppresion and immunodeficiency. On another hand, FIV has a marked tropism towards TCD4+ lymphocytes, triggering a characteristic immunodeficiency, but a frequent neurotropism has also been described. In both viruses, serological diagnostic is a routine procedure; however, in some situations it is not possible to identify correctly the infected cats. Recent studies have included Polymerase Chain Reaction (PCR) as a diagnostic method, opening a possibility to decreasing diagnostic errors for FeLV, but its effectiveness for FIV detection is still being discussed. The purpose of the present article is to provide updated and precise information about epidemiological, clinical and diagnostic aspects of FeLV and FIV in domestic cats.